Tensile properties and weld dimension of dissimilar material joint between AA5083 and AA6061 with coldarc gas metal arc welding - Manickavelu, Gogulan P. (2021)
AA 5083 and AA6061 dissimilar Aluminium Alloy are joined by ColdArc GMAW. Both aluminium from 5XXX and 6XXX series which commonly used in high strength products. The welding carried out by using EWM Robot Welding. ColdArc setting used in the EWM Robot Welding for this experiment. The joint type used was butt joint with 3mm material thickness. Furthermore, the design matrix for parameters obtained from the Taguchi method. The parameters are taken as factors and output are tensile testing and hardness test. Finally, the Taguchi Method method utilised in analysing the data or result obtained from the experiment. ColArc GMAW utilised in this experiment to identify the difference in the strength of welded joints and Heat-Affected Zone (HAZ). This is because normal fusion welding exerts a high rate of heat input while colArc reduces heat input at the arc. The heat input from the welding has a severe effect on the coarse grain structure and inter- metallic development in the weld zone. The high and low heat input influences the strength of the HAZ of the material. Besides, the tensile properties of the material face severe changes according to the level of heat input and other parameter settings. Parameters such as current, voltage, arc travel speed and type of filler wire can affect this strength of the material. Besides, heat input also can influence the dimension of weld bead on the weld- ment and penetration of the weldment. The high and low of bead width and bead height are affected by the heat input from the setting of parameters. Therefore, to ensure this prob- lem can be solved by using optimised parameters.